I don't want to! - Mooney, Bel; Chamberlain, Margaret (Egmont London, 2002)
Kitty's favourite word is no! She doesn't want to clean her teeth, eat her vegetables or play with boring Melissa. She can't stop saying no, but when Dad tells her he doesn't want to hear her say yes she discovers that's what she does want to say!